The influences of the image of women in the construction of text structure and Production of Aesthetics in Sherko Bekas's (Mlwanke = Bracelet) Divan - Mira, Ahmad Muhammad Rashid; Muhammad, Emdad Abdulwahid; Aziz, Aryan Sdiq; Abdulla, Kanyaw Bakr; Abdulla, Mawdud Jabar (Universitas Islam Negeri Raden Intan Lampung, 2023)
This research, entitled (The Influence of Women's Images in the Construction of Text Structure and Aesthetic Production in Sherko Bekas's (Mlwamke) divan. It is an attempt to present the poet's poetic language and then identify the characteristics that characterize feminism and women's rebellion. In addition to presenting the poetic language, what is more important in the research is to show the image of women in the poet, in terms of revealing the dimensions related to the poetic texts in the book, following the descriptive analytical approach. The study is divided into two main parts. The second part is devoted to imagination, metaphor and aesthetics. as the constituent of the image of women in the diwan. The scientific aim of this research is to try to determine the image of women at the gender, social, religious and political levels and present its dimensions in a scientific manner, in addition to determining the levels of women's image, Because women have an active participation in the entire divan.